A checklist of parasites in non‐native populations of rotan Perccottus glenii Dybowski, 1877 (Odontobutidae). (13th September 2013) - Sokolov, S. G.; Reshetnikov, A. N.; Protasova, E. N.
Summary This review presents data on diversity, prevalence, and distribution of protistan and metazoan parasites in non‐native populations of the rotan Perccottus glenii. The information was collected using peer reviewed journals, difficult to access grey literature, and original data of the authors. As a whole, 70 literature sources from 1971 to 2012 were analyzed. The data originate from five of the 17 countries already colonized by P. glenii. A total of 97 parasite species/taxa are listed, each with the location in/on the host, geographical localities, countries, and literature sources. Where available, the number of fish examined as well as the prevalence and range of infection intensity are cited from the respective sources. Attention is given to host‐specific parasites because the rotan is a vector of their new geographical distribution. The current state and perspectives for further research are discussed.